Food safety in Kenya: Focus on dairy - Grace, Delia; Alonso, Silvia; Mutua, Florence K.; Hoffmann, Vivian; Lore, Tezira A.; Karugia, Joseph T. (International Livestock Research Institute, 2020)
Infographic created for Voice for Change Partnership, Food and Nutrition Security Dissemination Forum: Evidence for Policy, Advocacy and Partnerships, Online Webinar, 8 July 2020.